ILO Convenstions and Migrant Workers: Construction of Protection in National Labor Law - Muslim, Shohib; Hadiwinata, Khrisna; Khoirunnisa, Rizqi; Hadiyantina, Shinta; Amin Ayub, Zainal (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The International Labor Organization has clearly regulated that human rights such as the right to work must be upheld and guaranteed. Therefore, no one should be prevented from working to meet their needs, whether domestically or abroad. The most crucial factor is the state's ability to safeguard its inhabitants, particularly those who work overseas, so that they can be treated with the respect and dignity befitting human beings. The private sector, represented by PTKIS, is given broad responsibilities by Law Number 18 of 2017 concerning the placement and protection of Indonesian workers abroad. However, Chapter VI of the law provides protection only during placement and does not include a comprehensive protection system. This study employs normative legal research using both a concept and statutory approaches. The study concludes that significant changes are required, including giving the government more authority to place and protect migrant workers. Up to now, there has been no clear definition of the extent or boundaries of this authority. It remains challenging to apply the development of legal frameworks and protections for migrant workers in line with the labour rights principles outlined in the ILO convention on the protection of all migratory workers to the issues encountered by workers overseas. The protection of migrant workers is frequently implemented in a fragmented and unsustainable way.